Involvement of human monogenic cardiomyopathy genes in experimental polygenic cardiac hypertrophy - Prestes, P R; Marques, F Z; Lopez-Campos, G; Lewandowski, P; Delbridge, L M D; Charchar, F J; Harrap, S B (Physiological genomics, 2018)
Hypertrophic cardiomyopathy thickens heart muscles, reducing functionality and increasing risk of cardiac disease and morbidity. Genetic factors are involved, but their contribution is poorly understood. We used the hypertrophic heart rat (HHR), a unique normotensive polygenic model of cardiac hypertrophy and heart failure, to investigate the role of genes associated with monogenic human cardiomyopathy. We selected 42 genes involved in monogenic human cardiomyopathies to study: 1) DNA variants, by sequencing the whole genome of 13-wk-old HHR and age-matched normal heart rat (NHR), its genetic control strain; 2) mRNA expression, by targeted RNA-sequencing in left ventricles of HHR and NHR at 5 ages (2 days old and 4, 13, 33, and 50 wk old) compared with human idiopathic dilated cardiomyopathy data; and 3) microRNA expression, with rat microRNA microarrays in left ventricles of 2-day-old HHR and age-matched NHR. We also investigated experimentally validated microRNA-mRNA interactions. Whole-genome sequencing revealed unique variants mostly located in noncoding regions of HHR and NHR. We found 29 genes differentially expressed in at least 1 age. Genes encoding desmoglein 2 ( Dsg2) and transthyretin ( Ttr) were significantly differentially expressed at all ages in the HHR, but only Ttr was also differentially expressed in human idiopathic cardiomyopathy. Lastly, only two microRNAs differentially expressed in the HHR were present in our comparison of validated microRNA-mRNA interactions. These two microRNAs interact with five of the genes studied. Our study shows that genes involved in monogenic forms of human cardiomyopathies may also influence polygenic forms of the disease.